Hypochondriasis: considerations for ICD-11 - Odile A. van den Heuvel (Brazilian Journal of Psychiatry, 2014)
The World Health Organization (WHO) is currently revisiting the ICD. In the 10th version of the ICD, approved in 1990, hypochondriacal symptoms are described in the context of both the primary condition hypochondriacal disorder and as secondary symptoms within a range of other mental disorders. Expansion of the research base since 1990 makes a critical evaluation and revision of both the definition and classification of hypochondriacal disorder timely. This article addresses the considerations reviewed by members of the WHO ICD-11 Working Group on the Classification of Obsessive-Compulsive and Related Disorders in their proposal for the description and classification of hypochondriasis. The proposed revision emphasizes the phenomenological overlap with both anxiety disorders (e.g., fear, hypervigilance to bodily symptoms, and avoidance) and obsessive-compulsive and related disorders (e.g., preoccupation and repetitive behaviors) and the distinction from the somatoform disorders (presence of somatic symptom is not a critical characteristic). This revision aims to improve clinical utility by enabling better recognition and treatment of patients with hypochondriasis within the broad range of global health care settings.